I don’t want to be a teacher: Factors restricting male students from entering the teaching profession - Christina Andin; Hafizah Harun; Rohana Hamzah; Khalid Johari (Penerbit UPM, 2017)
This study is motivated by concern about the small number of male school-leavers entering the teaching profession in Malaysia. It is important to determine empirically the reasons why the teaching profession is not popular as their career option, to see whether this can inform us about measures that can be taken to increase the involvement of men in the teaching profession. This study seeks to explore the factors that restrict male students from choosing teaching as a career. A total of 85 first-year male engineering students completed a questionnaire in which they were asked to rate factors that restricted them from entering the teaching profession. The findings of the study revealed that the most significant factor was associated with social influences, followed by poor job conditions, negative perceptions of the teaching profession and limited personal value. This paper proposes that halting the decline in numbers of male teachers is a task that requires the intervention and contribution of not only schools and policy makers but also parents and society, and recommends that effective strategies for attracting young male school leavers to join the teaching profession be developed.